ChemInform Abstract: Indole Synthesis by Rhodium(III)‐Catalyzed Hydrazine‐Directed C—H Activation: Redox‐Neutral and Traceless by N—N Bond Cleavage. Issue 16 (22nd April 2014) - Zhao, Dongbing; Shi, Zhuangzhi; Glorius, Frank
Abstract This reaction yields unprotected indoles from 2‐acetyl‐1‐arylhydrazines and alkynes without the need for an external oxidant.